Hepatoprotective Effect of Ethanolic Extract of Pegagan Leaves (Centella asiatica L. Urban) on Histological Damage of Hepatocyte on Mice Model induced by Parasetamol - Naila Shofwati Putri; Suyatmi .; Ratih Puspita Febrinasari (Nexus Biomedika, 2015)
Background: Pegagan leaves (Centella asiatica L. Urban) contain antioxidative compounds that can protect hepatocytes from free radicals. The aim of this research was to know the hepatoprotective effect of ethanolic extract of pegagan leaves (Centella asiatica L. Urban) on histological damage of hepatocyte on mice model induced by paracetamol. Methods: This study was an experimental laboratory with the post test only control group design. Samples were 30 male Swiss webster mice, with 2-3 months old and 20 gr body weight divided into 5 groups equally. KN and KI were given distilled water for 14 days. In addition, KI was also given paracetamol in dose 5.07 mg/20 gbw on the 12th, 13th, 14th day. KP1, KP2, and KP3 were given ethanolic extract of pegagan leaves in dose 5 mg, 10 mg, and 20 mg per 20 gbw respectively for 14 days and paracetamol in dose 5.07 mg per 20 gbw on the 12th, 13th, 14th day. On the 15th day, mice were sacrificed and their livers were taken for preparation with paraffin block method and stained with HE. The features of histological damage of hepatocyte were assessed by counting the numbers of nucleus damage of hepotocyte (pyknosis, karyorrhexis, karyolysis) of 100 cells in the sentrolobular zone. The data were analyzed by One-way ANOVA test and Post Hoc LSD test. Results: The means of histological damage of hepatocyte were 16.08 5.160; 66.00 3.275; 44.58 5.583; 31.67 2.188; 26.17 3.810 for KN, KI, KP1, KP2, KP3 respectively. The result of One-Way ANOVA test was *p = 0.000. The result of Post Hoc LSD test showed a significant difference between five groups, *p = 0.000 for KN-KI, KN-KP1, KN-KP2, KN-KP3, KI-KP1, KI-KP2, KI-KP3, KP1-KP2, KP1-KP3 and *p = 0.002 for KP2-KP3. Conclusion: The ethanolic extract of pegagan leaves can prevent histological damage of hepatocyte on mice model induced by paracetamol. Keywords: ethanolic extract of pegagan leaves, paracetamol, histological damage of hepatocyte